Progesterone for the prevention of preterm birth - an update of evidence-based indications - Kuon, Ruben-Jeremias; Scharli, Pauline; Rath, Werner (Geburtshilfe und Frauenheilkunde, 2019)
The prevention and treatment of preterm birth remains one of the biggest challenges in obstetrics. Worldwide, 11% of all children are born prematurely with far-reaching consequences for the children concerned, their families and the health system. Experimental studies suggest that progesterone inhibits uterine contractions, stabilises the cervix and has immunomodulatory effects. Recent years have seen the publication of numerous clinical trials using progestogens for the prevention of preterm birth. As a result of different inclusion criteria and the use of different progestogens and their methods of administration, it is difficult to draw comparisons between these studies. A critical evaluation of the available studies was therefore carried out on the basis of a search of the literature (1956 to 09/2018). Taking into account the most recent randomised, controlled studies, the following evidence-based recommendations emerge: In asymptomatic women with singleton pregnancies and a short cervical length on ultrasound of ≤ 25 mm before 24 weeks of gestation (WG), daily administration of vaginal progesterone (200 mg capsule or 90 mg gel) up until 36 + 6 WG leads to a significant reduction in the preterm birth rate and an improvement in neonatal outcome. The latest data also suggest positive effects of treatment with progesterone in cases of twin pregnancies with a short cervical length on ultrasound of ≤ 25 mm before 24 WG. The study data for the administration of progesterone in women with singleton pregnancies with a previous preterm birth have become much more heterogeneous, however. It is not possible to make a general recommendation for this indication at present, and decisions must therefore be made on a case-by-case basis. Even if progesterone use is considered to be safe in terms of possible long-term consequences, exposure should be avoided where it is not indicated. Careful patient selection is crucial for the success of treatment.
Gesehen am 23.04.2020